Optimizing Work Safety: Campaign using the Facet Model of approach Effect and the assessment sheet potential hazard IDEACM - Ridwan Gucci, Dinda Okta Dwiyanti; Nalendra, Muhammad Adi Sukma (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The macro-ergonomic approach integrates human factors with cultural and environmental aspects in occupational health and safety (K3). This approach emphasizes the critical role of culture, advocating for practitioners to adhere rigorously to workplace norms. A well-designed campaign targeting a homogeneous audience can significantly enhance the implementation of a harmonious safety culture. Through persuasive communication strategies that resonate emotionally and encourage changes in attitudes and behaviors, such campaigns utilize various appropriate media to convey the importance of adhering to company safety regulations. Furthermore, macro-ergonomics aims to foster a health and safety culture by clearly communicating organizational rules. This study explores the impact of persuasive campaigns on achieving zero accidents by conducting a case study at PT.X in Batam. It investigates potential hazards using macro-ergonomics and examines the effectiveness of a persuasive campaign aimed at the target audience at PT Batam-based Corner, focusing on the application of visual communication design in reinforcing K3 compliance. This integrated research approach underscores the need for collaborative efforts in industrial engineering to enhance safety outcomes. Keywords: Health And Safety Work, Campaigns, Ergonomics Macro